Refractive indices of binary mixtures of diglycolamine - water at various temperatures - Eduardo I. Concepción (Chemical Thermodynamics and Thermal Analysis)
In this work, the refractive indices nD, refractive index deviations Δ nD, molar refractions Rm and excess molar refractions REm were determined over the full range of compositions for the Diglycolamine-water binary mixture. Experimental measurements of these properties were carried out at atmospheric pressure and at temperatures ranging from 293.15 to 333.15 K. Excess molar refractions REm and refractive index deviations Δ nD have been fitted to the polynomial Redlich-Kister equation. The refractive indices have been compared with those predicted by the mixing rules proposed by: Lorentz-Lorenz (L-L), Gladstone- Dale (G-L), Eykman (E), Arago-Biot (A-B), Eyring-John (E-J), Bruggeman (B), and Oster (OS), in order to verify their validity for the Diglycolamine-water binary system. The experimental values of the refractive indices agree well with all the previous relationships, with the relationship of Oster (OS) and Gladstone-Dale (G-L) with which better results are obtained.